2018
DOI: 10.3329/bjp.v13i2.36133
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of phytoconstituents and evaluation of biological potentials of Berberis hispanica from Algeria

Abstract: <p class="Abstract">The aim of this study was to isolate the phytoconstituents and evaluate the biological activities of <em>Berberis hispanica</em>. Three phenolic compounds (tamarixetin, caffeic acid and rutin)  were isolated from <em>B. hispanica</em>. The structures of the pure compounds were elucidated by spectroscopic and mass-spectrometric analyses, including 1D-, 2D-NMR, and HPLC-TOF/MS. In addition, antimicrobial, anti-oxidant and anti-proliferative effects of the extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In previous literature, total bioactive components for several Berberis species have been reported. However, most studies were conducted on Berberis fruits [30,31,32]. A recent study reported that the methanol extract (80%) of Berberis orthobotrys contained more phenolics and flavonoids than the water extract [33], in agreement with our results.…”
Section: Resultssupporting
confidence: 91%
“…In previous literature, total bioactive components for several Berberis species have been reported. However, most studies were conducted on Berberis fruits [30,31,32]. A recent study reported that the methanol extract (80%) of Berberis orthobotrys contained more phenolics and flavonoids than the water extract [33], in agreement with our results.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, we can confirm that the chemical content of the studied plant is strongly correlated to the biological outcomes. It was demonstrated that the rutin and tamarixetin contained in Berberis were responsible for the inhibition of cancer cell lines in a concentration-or time-dependent manner by inducing apoptosis and blocked cell cycle progression at the G2-M phase [10]. Antiproliferative activity in breast (MCF-7), colon (Caco-2), and pancreas (BxPC-3) cancer cell lines induced by Genus berberis was well reported elsewhere (21).…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Analysismentioning
confidence: 72%
“…Fernández-Poyatos et al (2020) [12] reported that the most abundant compounds found in B. hispanica are phenolic acids, primarily chlorogenic acid and other caffeoylquinic acids. These compounds have been reported to have antioxidant effects [10,23]. Moreover, these compounds have also been shown to possess an in vivo and in vitro anticancer activity in various cancerous cell lines including MCF-7, HCT-116, Hep-G2, and PC-3.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%
See 2 more Smart Citations